Scrum Board Application Development Using MERN via Scrum Method and AHP Algorithm for Software Project Management - Sanjaya, Hafiyan Rizqi; Pamungkas, R Wisnu Prio; Sinlae, Fried (Jurnal Kecerdasan Buatan dan Teknologi Informasi, 2026)
Agile Scrum is widely adopted in software engineering, yet teams frequently face challenges such as unstructured backlog management, limited sprint progress visibility, and highly subjective priority decisions. This study addresses these critical issues by developing an Android-based project management application that integrates Scrum Board functionality with the Analytical Hierarchy Process (AHP) for objective and measurable backlog prioritization. Built on the MERN Stack architecture (MongoDB, Express.js, React Native, Node.js), the system was developed iteratively through four one-week sprint cycles. The integrated AHP module evaluates backlog items using three weighted criteria: Urgency (0.65), Complexity (0.23), and Work Value (0.12). System correctness and reliability were rigorously validated using Black Box Testing methodologies. The results demonstrate that the AHP module yields a highly consistent priority ranking (Consistency Ratio = 0.017), successfully identifying the Login Feature as the highest priority with a score of 4.42. Furthermore, functional testing confirmed 100% compliance across all core scenarios, including user authentication, sprint creation, task assignment, and Scrum Board status updates. This research successfully unifies Agile Scrum management and AHP decision support within a single, cohesive mobile application. By embedding objective decision-making directly into the daily project workflow, the system effectively eliminates reliance on external prioritization tools, bridging the current project management tool gap. Ultimately, it provides a scalable, replicable architecture suitable for future enhancements, such as real-time collaboration, push notifications, and multi-project portfolio management.